Evaluasi Program Predator Kabupaten Sumedang - Dhesti Widya Nurhasanah Ningrum; M. Zamzami M. Zamzami (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The Motor Cycling Electronic ID Card Recording Service Program (PREDATOR) is one of the innovation programs that has the aim of making people into the category of elderly, disabled and ODGJ who cannot record their Electronic ID cards at the Disdukcapil or in the sub-districts have an Electronic ID card. This article aims to determine the evaluation of the implementation of the Predator program in Sumedang Regency. The problem is focused on Program Evaluation. The theoretical reference used is the Program Evaluation Dimension of Brigman and Davis in Tayibnapis (2000), which consists of Input, Process, Output, and Outcome. Data was collected by means of library research and field studies (observations, interviews, and documentation) which were then analyzed qualitatively. The results of the study indicate that the implementation of the Predator program in Sumedang Regency has been going quite well and there are several obstacles in its implementation such as inadequate facilities and infrastructure and there is no definite schedule for the provision of Predator services due to the absence of special Predator service officers so that services are provided when there is a request. from the District.